Sinusitis-Induced Guillain-Barré Syndrome - Omer J Ungar; Anat Wangier; Nurit Omer; Ilan Koren (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Guillain-Barré syndrome (GBS) is a heterogeneous, relatively uncommon, post-infectious, immune-mediated polyradiculoneuropathy. It is estimated to affect 1.1-1.8/100,000/year in Europe and North America [1]. Historically, GBS was considered to be a single disorder, but it is currently classifi ed into six clinically distinct subtypes. It can manifest as cranial nerve involvement, including bilateral facial palsy,which is observed in 45-75% of cases [2]. In most instances, bilateral facial palsy or facial diplegia (FD) manifests either as bilateral Bell's palsy or as part of the presentation of GBS [3]. Plasmapheresis or the administration of intravenousimmunoglobulin (IVIG) are the gold standard therapies for the demyelinating form of GBS and probably for the other subtypes as well, and they reportedly shorten the course of the disease [4]. Despite recent progress in therapeutic management, GBS still results in an in-hospital mortality rate of over 2.5% and a>9% need for endotracheal intubation, which is known to be apredictor of mortality [5]. We describe the clinical presentation, radiologic fi ndings and management of a unique case of acutepansinusitis-induced GBS with isolated FD.